Impact of medical innovations on quality of care in low income settings - Sigala, MD, Gana Romanus; Michel Tchadie, Alain (International Journal of Scientific Research and Management (IJSRM), 2024)
Access to high-quality healthcare remains a challenge in low-income settings, primarily due to resource constraints and limited access to medical innovations. This systematic review examines the impact of medical innovations on the quality of care in low-income settings. Through a comprehensive analysis of relevant literature, this paper highlights the various medical innovations that have been implemented in low-income settings and evaluates their effectiveness in improving healthcare outcomes and patient satisfaction.The review identifies three broad categories of medical innovations: technological innovations, innovative healthcare delivery models, and novel treatment modalities. Technological innovations encompass a wide range of advancements, including telemedicine, mobile health (mHealth) applications, and point-of-care diagnostics. These innovations have shown promise in improving access to healthcare services, enhancing diagnostic accuracy, and facilitating remote monitoring and follow-up care in low-resource settings.Innovative healthcare delivery models, such as community health worker programs, task shifting, and mobile clinics, have also been implemented to overcome barriers to healthcare access in low-income settings. These models prioritize community engagement, decentralization of services, and task delegation to non-physician healthcare providers to expand coverage and reach underserved populations.Furthermore, novel treatment modalities, including affordable and portable medical devices, point-of-care testing kits, and low-cost medications, have been developed to address the specific healthcare needs of low-income populations. These innovations aim to improve treatment efficacy, reduce treatment costs, and minimize the burden of disease in resource-limited settings.The review synthesizes evidence from a diverse range of studies to assess the impact of these medical innovations on healthcare outcomes and patient satisfaction. Key findings suggest that while medical innovations hold promise in enhancing quality of care, several challenges including limited resources, infrastructure constraints, and training requirements need to be addressed to maximize their impact.The paper concludes by emphasizing the importance of tailored approaches and sustainable strategies for implementing medical innovations in low-income settings. By fostering partnerships, leveraging existing infrastructure, and investing in capacity building initiatives, stakeholders can effectively integrate medical innovations into healthcare delivery systems and improve access to high-quality care for underserved populations.This systematic review contributes to the growing body of literature on healthcare innovation and provides valuable insights for policymakers, healthcare providers, and researchers seeking to address the healthcare needs of low-income populations and achieve health equity on a global scale.